(3cJGH aj Gdadcs - (3GdSGYOj, eMeO Hf eGLO,s
(3ChdgG (B:s
(3edc jhe GdOjf EjGc fYHO hEjGc fSJYjfgPG GdcJGH aj Yde Gdadc GdHMQ ef JCdjaeMeO Hf eGLO GdSGYOj eYde GdHQ hGdHMQ aj HjGf eYQaI GdWhd hGdYQV aj GdLeY hGdJfRjd eG Hjf GdLGg hGdeWdY GdYQV eY GdYQV HLeY Shi hGdWhd eY GdWhd Shis
(3BNQgG (B:s
(3hdG jaYd CjVG Ydi GdchcH GdPj jchf aj GdWGdY EPG de jSbW Yf OQLI aEf GdVejQ Ydi Pdc GdchcH hOdGdI Hjfg GdPj jfXQ Edjg fXQ EdjgeG LejYG GdOdjd GdKGfj ef GdbhI(B: (3GdOdjd GdKGfj OhQ ShS (B((3cPG(B) (3hZjQg efs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3gjFIs